A new optical intra-tissue fiber irradiation ALA-PDT in the treatment of acne vulgaris in rabbit model: improved safety and tolerability - Qian Wang; Can Jiang; Wei Liu; Jin Chen; Xinyu Lin; Xiangning Huang; Xiling Duan (Sociedade Brasileira de Dermatologia, 2017)
Abstract Background: Photodynamic therapy with topical aminolevulinic acid (ALA-PDT) has been suggested to be effective in treatment of acne vulgaris. However, adverse events occur during and after treatment. Objectives: To compare the efficacy and tolerability of optical intra-tissue fiber irradiation (OFI) ALA-PDT versus traditional ALA-PDT in treatment of acne vulgaris in rabbit models. Methods: Twenty-five rabbits of clean grade were used. Twenty rabbits were randomly selected to establish acne model and the other five were used as control. Rabbits in model group (40 ears) were further divided into four groups (10 ears/group): I, OFI-ALA-PDT with the head of optical fiber inserted into the target lesion (intra-tissue); II, traditional ALA-PDT group; III, OFI group; IV, blank control group without any treatment. Uncomfortable symptoms, adverse events, and effectiveness rates were recorded on post-treatment day 14, 30, and 45. Results: On post-treatment day 14, the effectiveness rate in OFI-ALA-PDT group was obviously higher than that of the other three groups (P<0.05). However, no improved effects were observed in OFI-ALA-PDT group on day 30 and 45. During the period of treatment, the frequencies of uncomfortable symptoms in ALA-PDT group were obviously higher than those in the other three groups (P<0.05). The adverse event rate in OFI-ALA-PDT group was obviously lower than that of the ALA-PDT group (P<0.05) Study limitations: The unblindness of the study and temporary animal models of acne induced may hamper the assessment and monitoring of the results, and future studies are still needed to clarify it further. Conclusion: The OFI-ALA-PDT group (intra-tissue irradiation) showed no improved efficacy on treating rabbit ear acne but had higher safety and better tolerability.